Advanced Beverage Can Crusher Machines: A Review - Elfasakhany, Ashraf (Asian Review of Mechanical Engineering, 2020)
Beverage Can crushing machine is a device, which is used to compact scrap metal Cansinto small size ones, and, in turn, the Canswould be reused later as new products. Many designs for the Can crushers are applied for such compacting process, some simple and other complicated. This work presents a review study for the advanced or up to date beverage Can crusher machines. Several issues described new designs for the advanced Cans crushing processes are presented in the current study.